Emotional Intelligence Mitigates the Effects of Customer Incivility on Surface Acting and Exhaustion in Service Occupations: A Moderated Mediation Model - Szczygiel, Dorota Daniela; Bazińska, Róz·a (Frontiers in Psychology, 2021)
This study contributes to the constantly accumulating evidence on the effects of customer incivility (CI) on service employee exhaustion. Previous research has demonstrated that surface acting (SA) acts as a mediating variable in the relationship between CI and exhaustion. This study extended prior findings in two ways. The results of Study 1 (315 retail sales employees, 62.2% female) demonstrated that SA mediates the positive relationship between CI and exhaustion while controlling for employees’ trait positive and negative affectivity. The results of Study 2 (292 customer service representatives, 51% female) supported a moderated mediation model demonstrating that trait emotional intelligence (EI) buffers the direct and indirect (through SA) effects of CI on exhaustion. Specifically, it was found that employees exposed to many uncivil customer behaviours but high in trait EI reported using less SA and, thus, experienced fewer exhaustion symptoms than their low in trait EI counterparts. These results highlight EI as an important personal resource that mitigates the adverse effects of CI on service employees’ exhaustion, and suggest that organisations should consider implementing EI training programmes for their frontline service employees.